Proposal of a new nomenclature for introns in protein-coding genes in fungal mitogenomes - Shu Zhang; Yong-Jie Zhang (IMA Fungus)
Abstract Fungal mitochondrial genes are often invaded by group I or II introns, which represent an ideal marker for understanding fungal evolution. A standard nomenclature of mitochondrial introns is needed to avoid confusion when comparing different fungal mitogenomes. Currently, there has been a standard nomenclature for introns present in rRNA genes, but there is a lack of a standard nomenclature for introns present in protein-coding genes. In this study, we propose a new nomenclature system for introns in fungal mitochondrial protein-coding genes based on (1) three-letter abbreviation of host scientific name, (2) host gene name, (3), one capital letter P (for group I introns), S (for group II introns), or U (for introns with unknown types), and (4) intron insertion site in the host gene according to the cyclosporin-producing fungus Tolypocladium inflatum. The suggested nomenclature was proved feasible by naming introns present in mitogenomes of 16 fungi of different phyla, including both basal and higher fungal lineages although minor adjustment of the nomenclature is needed to fit certain special conditions. The nomenclature also had the potential to name plant/protist/animal mitochondrial introns. We hope future studies follow the proposed nomenclature to ensure direct comparison across different studies.